2019
DOI: 10.1002/term.2986
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a dermis–fat composite in vivo: Optimizing heterogeneous acellular dermal matrix with in vitro pretreatment

Abstract: Dermis–fat composite tissues have been widely used in plastic and reconstructive surgery and were previously constructed using hydrogel‐type scaffolds. The constructs can be used for in vitro cosmetic and pharmaceutical testing but are not mechanically strong enough for in vivo applications. In this study, we used heterogeneous (porcine) acellular dermal matrix (PADM) as dermal layer scaffold. PADM was pretreated with the laser micropore technique and then precultured with rat adipose‐derived stem cells (rADSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…This partially explains why the higher VEGF and VEGFR2 expression groups did not show the strongest vascularization (Figure 3). The forementioned results confirm that addition of a proper amount of CCL2 (specifically 50 ng/ml) to the co-culture system significantly enhanced angiogenesis of the co-culture system while more mature prevascularization in vitro has been reported to result in better tissue construction in vivo (Sasagawa et al, 2014;Zhu et al, 2020).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This partially explains why the higher VEGF and VEGFR2 expression groups did not show the strongest vascularization (Figure 3). The forementioned results confirm that addition of a proper amount of CCL2 (specifically 50 ng/ml) to the co-culture system significantly enhanced angiogenesis of the co-culture system while more mature prevascularization in vitro has been reported to result in better tissue construction in vivo (Sasagawa et al, 2014;Zhu et al, 2020).…”
Section: Discussionsupporting
confidence: 61%
“…hADSCs from passages two to four were used for the experiments. Adipogenic differentiation strategy was modified according to the published article and our experience (Wang et al, 2018;Yang et al, 2021;Zhu et al, 2020). Briefly, hADSCs were cultured to overconfluence for 3 days, and then GM was replaced with adipogenic differentiation medium (ADM)-A consisting of low-glucose DMEM containing 10% FBS, 100 μg/mL P/S, 0.5 mM 3-Isobutyl-1methylxanthine (IBMX; Sigma-Aldrich), 1 μM dexamethasone (Sigma-Aldrich), 10 μM insulin (MedChemExpress), and 200 μM indomethacin (Sigma-Aldrich) for 3 days with or without CCL2 (10, 50, and 100 ng/ml).…”
Section: Cell Culturementioning
confidence: 99%
“…After 24 h of co-culture (processing with the above method found in the “ Indirect co-culture by a Transwell system ” section), total RNA was extracted using EZ-press RNA Purification Kit (B0004D, EZBioscience, Roseville, USA) according to the manufacturer’s instructions [ 31 33 ]. RNA purity was evaluated by calculating the A260/A280 ratio, which should be between 1.8 and 2.0.…”
Section: Methodsmentioning
confidence: 99%
“…Drilling can directly transform the ADM structure and adjust its pore size and porosity, thus improving its permeability. In practical application, drilling can increase the contact area between ADM and cells, providing favorable conditions for cell adhesion and migration into the ADM [41]. Laser micropore ADM grafting in combination with split thickness autografting can improve wound healing, and implantation studies have reported vascular infiltration and slow cell growth [42].…”
Section: Effect Of Modification On Microstructurementioning
confidence: 99%